POSHAN's abstract digest on maternal and child nutrition research - Issue 35 - Avula, Rasmi (International Food Policy Research Institute, 2020)
This issue of Abstract Digest brings to you a set of interesting articles on stunting burden, drivers, and learnings from countries that have been successful in reducing stunting, including a case study on Chhattisgarh. In addition, there are studies on anthropometric data quality assessment, and a study describing the health system components required for the delivery of nutrition-specific interventions. This issue also includes studies on COVID-19 and its implications for child nutrition. In this edition, we have included a Call for Action issued by leaders of four UN agencies to protect children's right to nutrition in the face of the COVID-19 pandemic. In India, a diverse group of nutrition stakeholders have pledged their renewed Commitment to Action for supporting efforts by the government and all of society.